Scope of Solidarity in Social Security Policy – Looking for Real Redistribution and Adequate Benefits - Tadeusz SZUMLICZ (Communications of International Proceedings, 2021)
The underlying rationale for security systems should be security understood as one of the basic human values. Financial sense of security is a vital value for households. In the theoretical part of considerations, it seems important to pay attention to the elements that determine the construction of the social security system in each shape. I list ten aspects of the social security scheme, and I describe them in detail from a systemic perspective. Finally, I assess the attitudes and social acceptance for given solutions. I pay particular attention to the scope of solidarity in social security policy, describing and explaining the issue of redistribution and benefits. The social security system can be either assistance- or insurance-focused. The construction of insurance coverage seems to be the most important. I present a sequence of reasoning from threat to the value of financial security up to the evaluation of the effectiveness of the possible private insurance solutions in social security system. Referring to the practical approach, I draw attention to the changes in the Polish social security system, since the political transition (1989). I suggest to discuss the important role of insurance in social security system, both social and private insurance, in complementary and supplementary sense.
Keywords: Social Security Aspects; Solidarity; Redistribution; Social Benefits